Self-Efficacy and Grit: The Key to Overcoming Procrastination in Thesis Writing - Mustika, Cica; Laily, Nadhirotul (Psikostudia : Jurnal Psikologi, 2025)
Academic procrastination was a significant obstacle in thesis completion often experienced by students, mainly due to low self-confidence and lack of perseverance in facing long-term tasks. This study aimed to determine the influence of Self-Efficacy and Grit on Academic Procrastination among students at Universitas Muhammadiyah Gresik during the thesis writing process. The research employed a quantitative approach using multiple linear regression methods and involved 75 students selected through purposive sampling. Data were collected using the Self-Efficacy scale, Grit scale, and Academic Procrastination scale. The results of the analysis showed that Self-Efficacy and Grit simultaneously had a significant influence on Academic Procrastination with a contribution of 58.2%. Partially, Self-Efficacy had a more dominant effect compared to Grit in reducing the tendency of academic procrastination. These findings confirmed that the higher the level of students' Self-Efficacy and Grit, the lower their level of academic procrastination. The implication of this research emphasized the importance of strengthening self-confidence and perseverance in educational intervention strategies to help students complete their final projects on time. Therefore, universities were recommended to develop psychological assistance programs and personal development training focused on enhancing Self-Efficacy and Grit as preventive efforts against procrastinative behavior. Prokrastinasi akademik merupakan hambatan signifikan dalam penyelesaian skripsi yang sering dialami mahasiswa, terutama akibat lemahnya keyakinan diri dan kurangnya ketekunan dalam menghadapi tugas jangka panjang. Penelitian ini bertujuan untuk mengetahui pengaruh Self-Efficacy dan Grit terhadap Prokrastinasi Akademik mahasiswa Universitas Muhammadiyah Gresik dalam proses penyusunan skripsi. Penelitian ini menggunakan pendekatan kuantitatif dengan metode regresi linier berganda, melibatkan 75 mahasiswa sebagai responden yang dipilih melalui teknik incidental sampling. Instrumen pengumpulan data menggunakan skala Self-Efficacy, skala Grit, dan skala Prokrastinasi Akademik. Hasil analisis menunjukkan bahwa Self-Efficacy dan Grit secara simultan berpengaruh signifikan terhadap Prokrastinasi Akademik dengan kontribusi sebesar 58,2%. Secara parsial, Self-Efficacy memiliki pengaruh yang lebih dominan dibandingkan Grit dalam menurunkan kecenderungan prokrastinasi akademik. Temuan ini menegaskan bahwa semakin tinggi tingkat Self-Efficacy dan Grit mahasiswa, maka semakin rendah tingkat prokrastinasi akademik yang mereka alami. Implikasi dari penelitian ini menunjukkan pentingnya penguatan keyakinan diri dan ketekunan dalam strategi intervensi pendidikan guna membantu mahasiswa menyelesaikan tugas akhir tepat waktu. Oleh karena itu, perguruan tinggi disarankan mengembangkan program pendampingan psikologis dan pelatihan pengembangan diri yang terfokus pada peningkatan Self-Efficacy dan Grit sebagai upaya preventif terhadap perilaku prokrastinatif.